2021
DOI: 10.1155/2021/2491116
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Feature Extraction of Ancient Chinese Characters Based on Deep Convolution Neural Network and Big Data Analysis

Abstract: In recent years, deep learning has made good progress and has been applied to face recognition, video monitoring, image processing, and other fields. In this big data background, deep convolution neural network has also received more and more attention. In order to extract the ancient Chinese characters effectively, the paper will discuss the structure model, pool process, and network training of deep convolution neural network and compare the algorithm with the traditional machine learning algorithm. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…e empirical results show that the prediction effect is good. Zhang [4] put forward different neural network models for different research topics in the research process of enterprise credit risk. Liu [5] mainly focused on the prediction of corporate failure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…e empirical results show that the prediction effect is good. Zhang [4] put forward different neural network models for different research topics in the research process of enterprise credit risk. Liu [5] mainly focused on the prediction of corporate failure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In static scenes, the background model can be preimaged without moving objects or noise. Different processing is performed on the current image frame and the background reference model, and the region of the moving object is determined by counting the change information in the histogram [12]. Therefore, the size, position, shape, and other related information of the moving object can be known.…”
Section: Image Object Extraction Algorithmmentioning
confidence: 99%
“…Gu and Zhang ( 2020 ) pointed out that the intelligent composition review system can help students develop the habit of repeated revision, but it should not be It is still necessary to have teacher guidance. Zhang and Liu ( 2021 ) study found that course assessment mechanisms, students' vocabulary levels, their perceptions of the feedback from the intelligent writing system, and the quality of the intelligent system itself affect students' use, and that students' motivation to learn English affects their learning outcomes in the automatic evaluation feedback system. Zhao et al ( 2017 ) concluded that at the individual level, students' familiarity with computers, online learning experience, existing language ability and writing level, and learning autonomy bring about different usage effects in the collaborative artificial intelligence system, but there are no related research topics.…”
Section: Introductionmentioning
confidence: 99%